ycgR and luxR genes are involved in Klebsiella pneumonia biofilm formation (2012)
Klebsiella pneumoniae is an important Gram-negative opportunistic pathogen that causes different nosocomial infections. Understanding the mechanisms involved in its ability to form biofilms and persist in different environments, can provide useful information in order to propose strategies for effective treatment and control. In this study, we analyzed the role of the ycgR gene involved in biofilm formation using the clinical strain K. pneumoniae LM21. The ycgR gene was found to be part of an operon together with the luxR-like gene. Deletion of ycgR and complementation analysis with the intact gene indicated that it was responsible for the observed phenotype. However, complementation with both ycgR and luxR increased biofilms with respect to the wild type strain, and even in a ycgR mutant background, suggesting that luxR might also play a role in biofilm formation. The YcgR protein contained a PilZ domain predicted to bind to the c-di-GMP second messenger, while LuxR had a DNA binding domain and was predicted to be a novel type of transcriptional regulator. Using fluorescence microscopy we found that the ycgR mutation affected adherence at early hours of biofilm formation and cell to cell adherence, since a co-incubation with the wild type strain did not promote integration into the formed biofilm. Electron microscopy showed that the ycgR mutant was nonfimbriated in aerobic conditions, even though gene expression of the fimbiral component mrkA gene was still evident. These results show that ycgR is involved in fimbriae production that in turn affects biofilm formation in K. pneumoniae. Additional work is needed to address the specific role of LuxR, its interaction with YcgR and role in biofilm formation under different incubation conditions.